Resilience in the Sandwich Generation: Islamic Family Law Perspectives on Coping with Dual Responsibilities - Safitri, Dea (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2025)
This study examines the phenomenon of the sandwich generation, individuals squeezed by the dual responsibilities of caring for their parents and raising their children simultaneously. This phenomenon creates significant multidimensional pressures, affecting their well-being and crucial life decisions. This research aims to analyze how the sandwich generation builds resilience and develops coping strategies amidst this double burden, particularly within the framework of Islamic family law values. This study employs a mixed-methods approach, combining quantitative data from questionnaires with qualitative data from in-depth interviews. The data is then analyzed through the theoretical frameworks of Family Resilience and Role Conflict. Data were collected from 50 individuals aged 25-50, both married and unmarried, who belong to the sandwich generation. The main findings indicate that the sandwich generation faces emotional, financial, and social challenges, which impact decisions such as delaying marriage (waithood). However, they are not passive; they actively build resilience through two main strategies: problem-focused coping (financial planning and division of responsibilities) and emotion-focused coping (strengthening spirituality and seeking social support). The central argument of this research is that resilience is a dynamic process that enables them to balance the demands of their dual roles, where Islamic values serve as a source of motivational strength and an ethical framework for navigating the dilemmas of responsibility. [Penelitian ini mengkaji fenomena generasi sandwich, yaitu individu yang terhimpit tanggung jawab ganda untuk merawat orang tua dan membesarkan anak sekaligus.  Fenomena ini menimbulkan tekanan multidimensional yang signifikan, memengaruhi kesejahteraan dan keputusan hidup krusial. Penelitian ini bertujuan menganalisis bagaimana generasi sandwich membangun resiliensi dan mengembangkan strategi adaptasi di tengah beban ganda, khususnya dalam kerangka nilai hukum keluarga Islam. Penelitian ini menggunakan metode campuran (mixed methods) yang menggabungkan antara pendekatan kuantitatif melalui kuisioner dan pendekatan kualitati melalui wawancara mendalam. Kemudian dianalisis melalui kerangka teori Ketahanan Keluarga dan Konflik Peran. Data diperoleh melalui wawancara terhadap 50 orang yang termasuk generasi sandwich usia 25-50 tahun yang sudah menikah atau belum menikah. Hasil utama menunjukkan generasi sandwich menghadapi tantangan emosional, finansial, dan sosial, yang berdampak pada keputusan seperti penundaan pernikahan (waithood). Namun, mereka tidak pasif, melainkan secara aktif membangun ketahanan melalui dua strategi utama: problem-focused coping (perencanaan keuangan dan pembagian tanggung jawab) dan emotion-focused coping (penguatan spiritualitas dan dukungan sosial). Argumentasi sentral penelitian ini adalah bahwa resiliensi merupakan proses dinamis yang memungkinkan mereka menyeimbangkan tuntutan peran ganda, di mana nilai-nilai Islam berfungsi sebagai sumber kekuatan motivasional dan kerangka etik dalam menghadapi dilema tanggung jawab.]